INFLUENCE OF ANTIBIOTICS ON IN VITRO MORPHOLOGICAL CHARACTERS OF RECALCITRANT POTATO CULTIVAR KUFRI JYOTI - EP, Venkatasalam (Potato Journal, 2016)
In the study, the effect of three different antibiotics viz., carbenicillin (50, 75, 100 and 125 mgl-1), cephotaxime (100, 150, 200 and 250 mgl-1) and kanamycin (30, 40, 50 and 60 mgl-1)against bacterial contaminants (Bacillus pumilus) and in vitro shoot growth of potato (Solanum tuberosum L.) recalcitrant cultivar Kufri Jyoti was evaluated. Efficacy of antibiotics to control bacterial contaminant differed greatly; cephotaxime and carbenicillin were found to be more effective as compared to kanamycin. Results showed that antibiotics and their concentrations not only affected the growth morphology of the microplant and also the bacterial contaminants.Â  The medium containing carbenicillin 75 mgl-1 and cephotaxime 150 mgl-1 significantly accelerated the microplant height; number of leaves, nodes and roots; root length and fresh as well as dry weight. However, carbenicillin 50 mgl-1 and cephotaxime 100 mgl-1 was also at par to above mentioned concentrations for most of the microplant growth parameters. During the experiment we also observed negligible bacterial contamination in the above said concentrations. Higher concentration beyond this level however, had detrimental effect on the growth and morphology of microplant. The cost of incorporating carbenicillin is ` 90 cephotaxime ` 170 per litre of culture medium.